A STUDY ON DEVELOPMENT OF EDUCATION OF SCHEDULED CASTE PEOPLE OF ASSAM - Das, Binita (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Indian education system has always thrived to bridge the gap in social category; still there remains large disparities, especially between the advantaged groups and the disadvantaged groups which have been almost away from education. A disadvantaged group refers to a population that is in a higher risk of experiencing negative effects or harm in specific situation, such as natural disasters or emergencies. Socio-culturally, Scheduled Castes, Scheduled Tribes, Other Backward Classes and Minorities are known as disadvantaged groups. Disadvantaged groups often face social discrimination, lack access to resources, face cultural differences and economic constraints which affect their educational and social journey. Education and development are the two sides of the same coin. Education is the most important factor for development of a person, a society, a state and a nation. In Assam, literacy rate of one of the disadvantaged classes, that is, Scheduled Castes is below the state average due to various factors. To have a healthy society, there is a need to uplift these classes. As it is seen, in respect of enrolment, retention, and transition rates, the Scheduled Castes children lag behind those children belonging to other categories. Poverty is a major problem in the education of Scheduled Castes. Education helps the weaker section by making them aware of their rights, duties and provisions for their development. Ultimately, education helps to improve and uplift their living standards in the society and empower them.